A New Method for Horizontal Axis Wind Turbine (HAWT) Blade Optimization - Mohammadi, Mohammadreza; Mohammadi, Alireza; Farahat, Said (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
Iran has a great potential for wind energy. This paper introduces optimization of 7 wind turbine blades for small and medium scales in a determined wind condition of Zabol site, Iran, where the average wind speed is considered 7 m /s. Considered wind turbines are 3 bladed and radius of 7 case study turbine blades are 4.5 m, 6.5 m, 8 m, 9 m, 10 m, 15.5 m and 20 m. As the first step, an initial design is performed using one airfoil (NACA 63-215) across the blade. In the next step, every blade is divided into three sections, while the 20 % of first part of the blade is considered as root, the 5% of last the part is considered as tip and the rest of the blade as mid part. Providing necessary input data, suitable airfoils for wind turbines including 43 airfoils are extracted and their experimental data are entered in optimization process. Three variables in this optimization problem would be airfoil type, attack angle and chord, where the objective function is maximum output torque. A MATLAB code was written for design and optimization of the blade, which was validated with a previous experimental work. In addition, a comparison was made to show the effect of optimization with two variables (airfoil type and attack angle) versus optimization with three variables (airfoil type, attack angle and chord) on output torque increase. Results of this research shows a dramatic increase in comparison to initial designed blade with one airfoil where two variable optimization causes 7.7% to 22.27 % enhancement and three variable optimization causes 17.91% up to 24.48% rise in output torque .Article History: Received Oct 15, 2015; Received in revised form January 2, 2016; Accepted January 14, 2016; Available online How to Cite This Article: Mohammadi, M., Mohammadi, A. and Farahat, S. (2016) A New Method for Horizontal Axis Wind Turbine (HAWT) Blade Optimization. Int. Journal of Renewable Energy Development, 5(1),1-8. http://dx.doi.org/10.14710/ijred.5.1.1-8